Analysis of the role of process innovation on export propensity in KIBS and non-KIBS firms in Colombia (2020)
The purpose of this paper is to analyze the role of the process innovation on export propensity in knowledge-intensive business services (KIBS) firms and non-KIBS firms in Colombia. For the empirical application, the authors use a unique primary data set drawn from the Global Competitiveness Project (GCP: www.gcp.org) that includes information for 57 Colombian KIBS for 2019. The authors use a binary choice model to test the proposed hypotheses on the relevance of KIBS and process innovation in explaining export propensity. The results showed a positive relationship between KIBS and business size with an export propensity, but this relationship is non-meaningful. Also, the findings showed a negative and non-significant relationship between a process innovation and business age with the probability to export. On the other hand, the evidence state that KIBS firms encourage the relationship between propensity to export and process innovation, which is to say that they are highly effective to increase the propensity to export. Finally, the industry increases the probability of export propensity. This study offers a new insight relating to KIBS, process innovation and their contribution to increasing export propensity. The findings of this paper offer relevant information to government policymakers to design strategies that promote export activity in Colombia.